(untitled) (Bangladesh Journal of Medical Science, 2017)
Horners syndrome is caused by injury to the ipsilateral cervical sympathetic chain. The etiology is multifactorial with many traumatic, malignant and iatrogenic causes. Iatrogenic Horners syndrome following thyroidectomy is one such rare but well known entity. We report a case of 50 year old female who underwent right hemi-thyroidectomy for a solitary thyroid nodule and later presented with features of Horners syndrome 11 days after the surgery. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.600-601